1999
DOI: 10.1530/jrf.0.1150357
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a cytosolic phospholipase A2 by ovine endometrium on days 11-14 of a simulated oestrous cycle

Abstract: Oxytocin stimulates the synthesis and secretion of PGF2\g=a\ from uterine tissues in vivo and in vitro late in the ovine oestrous cycle. The synthesis of eicosanoids is dependent upon the availability of free arachidonic acid which is released through the activity of arachidonate releasing phospholipases. In the present study, the following hypothesis was tested: the ovine endometrium expresses a cytosolic phospholipase A2 (cPLA2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
2
3
0
2
Order By: Relevance
“…This finding is consistent with results reported by Binelli et al [30] in that it took about 12 h of culture with rbIFN-to notice inhibitory effects on PLA 2 . In the present experiments, cultures were terminated within 5 h. Graf et al [47] showed similar results for PLA 2 mRNA expression in the ewe upon treatment with oxytocin. We also investigated the phosphorylation of Raf-1 and ERK-1/2.…”
Section: Discussionsupporting
confidence: 80%
“…This finding is consistent with results reported by Binelli et al [30] in that it took about 12 h of culture with rbIFN-to notice inhibitory effects on PLA 2 . In the present experiments, cultures were terminated within 5 h. Graf et al [47] showed similar results for PLA 2 mRNA expression in the ewe upon treatment with oxytocin. We also investigated the phosphorylation of Raf-1 and ERK-1/2.…”
Section: Discussionsupporting
confidence: 80%
“…Our previous studies have shown that there were increased levels of estradiol receptor a, OTR, cPLA 2 , and COX-2 in the ovine cervix during the periovulatory period of the estrous cycle [18]. These observations are consistent with those of other groups who have also reported high levels of these proteins during the periovulatory period in the cervix [14,[19][20][21] or uterus [22] and provide evidence to support our hypothesis that the reproductive hormones (17b-estradiol, FSH, and oxytocin) collectively regulate cervical relaxation by stimulating COX-2-mediated synthesis of cervical PGE 2 .…”
Section: Introductionsupporting
confidence: 90%
“…Lysates of incubated cervical tissue gave a single band at approximately 100 to 110 kDa corresponding to the molecular weight of ovine cytosolic PLA 2 [22]. There were no significant differences in the expression of cPLA 2 among control explants and those treated with either FSH or 17b-estradiol (Fig.…”
Section: Tissue Expression Of Cplamentioning
confidence: 84%
“…-DESNOYERS et al, 1995;TYSSELING et al, 1998;ARNOLD et al, 2000; experimento 2 da presente tese). Em outros estudos a tapsigargia, um potente inibidor da atividade cálcio APTase, estimulou a síntese de PGF2α em explantes endometriais bovinos (TYSSELING et al, 1998;BURNS;HAYES;SILVIA, 1998) JORGE et al, 2003) e 18° dias do ciclo estral (RICO et al, 1981;KNICKERBOCKER et al, 1982). Assim, sugere-se que a síntese de PGF2α estimulada pelo E 2 , estaria na dependência de outros fatores endógenos presentes no organismo animal, condição que não seria reproduzida em um sistema de cultivo de células, uma vez que os demais fatores endógenos estariam ausentes.…”
Section: 7 7 M Mo Od De El Lo O E Ex Xp Pe Er Ri Im Me En Nt Ta Aunclassified
“…O elemento de resposta típico contém 5'-GGTCAnnnTGACC-3' como a seqüência de nucleotídeos necessária para que haja a ativação da transcrição do gene em resposta ao estradiol (DRISCOL et al, 1998). -DESNOYERS et al, 1995;BURNS et al, 1997;BURNS;HAYES;SILVIA, 1998;MANN, 2001 FAGAN;GOLBERG, 1986;GOFF, 1990;SLAMA;VAILLANCOURT;GOFF, 1994 Antes de iniciar os ensaios preparar uma planilha contendo o número dos tubos com a identificação dos conteúdos. As amostras devem ser divididas eqüitativamente entre os ensaios equivalente a um determinado experimento, animais e número da amostra de plasma coletada em série dentro de um mesmo ensaio.…”
Section: DI Is Sc Cu Us Ss Sã ãO O G Ge Er Ra Al Lunclassified